Collaborative project-based learning to train students for conducting the training project for older adults - Phetcharee Rupavijetra; Prachyanun Nilsook; Jira Jitsupa; Tipparat Nopparit (International Journal of Evaluation and Research in Education (IJERE), 2022)
This research aimed to study the results of collaborative project-based learning by students studying the training technique course to conduct training programs for older adults in state home care in Chiang Mai, Thailand. The population consisted of 40 undergraduate students from different faculties and years. The instruments used for data collection consisted of the lesson plan of the training technique course, student behavior form, journal form after teaching, student products, student reflection journals, the questionnaire to gauge the level of satisfaction of students, writing and presenting reflections on students’ learning, and training evaluation based on the level of satisfaction of the older adults. The research separated students into two groups based on different faculties, each group was composed of 20 students, and they could learn better in a small group. Data were analyzed by using content analysis, statistical calculation, and percentage, and were presented in the form of a description and table. The findings showed the results of the collaborative project-based learning to train students for conducting training projects for older adults successful. The students had a change in their attitudes, behaviors, knowledge, skills, and experience in conducting training, their satisfaction showed at the highest level (97.50%). Students were satisfied with the project-based learning at the highest level (90%), and especially the opportunity to gain knowledge and experience from conducting training programs at the highest level (95%). The older adults’ satisfaction from participating in two training programs conducted by the students was at the highest level (100%) too.